The Effect of Agility Training on Soccer Dribbling Skills Among Persije FC Players in South Bengkulu Regency - Akhmad Banda Niji; Feby Elra Perdima; Ajis Sumantri (Educative Sportive, 2026)
This study aims to determine the effect of agility training on soccer dribbling skills among Persije FC players in South Bengkulu Regency. Using a total sampling method, the study included 15 Persije FC players from South Bengkulu Regency. This experimental study employed a one-group pretest-posttest design, a pre-experimental design that involves a pretest (test administered before treatment) and a posttest (test administered after treatment) within a single group. Data were collected using test scores. Descriptive data analysis and the t-test were used. The results of this study indicate that agility training has an effect on the ball-dribbling skills of Persije FC players in South Bengkulu Regency, with a calculated t-value of 2.959 and a critical t-value of 1.761, at a significance level of α = 0.05 and df = 14.